Consumers’ purchase intention and feedback for online-to-offline ecommerce: A comparison between local and foreign university students in Malaysia - Wong, Wen Huei (2019)
With the improvement of technology year by year, the ways people purchase goods and services changed accordingly. Online-to-Offline (O2O) e-commerce is the new online purchase platform for people where consumers could purchase online and receive goods and services offline. By this, consumers can physically touch and feel the goods and services while return spoiled products to the seller directly. Due to O2O e-commerce is still new in Malaysia, this research is aim to determine factors that influence customer satisfaction and the influence of customer satisfaction towards consumers’ purchase intention and feedback on O2O e-commerce in view of Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). Besides, this research also investigating the differences between local and foreign university students on purchase intention and feedback towards O2O e-commerce. Moreover, questionnaires were used to collect data from 298 respondents who were university students in Malaysia through social media platform. Meanwhile, descriptive and inferential analysis will be use to analyse the data collected for this research and all the IVs are significantly influencing customer satisfaction while there is a difference between local and foreign university students on purchase intention and feedback. In brief, the results from this research will beneficial the managerial who doing O2O e-commerce as they could know the factors that influencing the customer satisfaction while purchase using O2O e-commerce and different perspectives of local and foreign university students on purchase intention and feedback towards O2O e-commerce.